2006
DOI: 10.1074/jbc.m510600200
|View full text |Cite
|
Sign up to set email alerts
|

PsbR, a Missing Link in the Assembly of the Oxygen-evolving Complex of Plant Photosystem II

Abstract: The oxygen-evolving complex of eukaryotic photosystem II (PSII) consists of three extrinsic nuclear-encoded subunits, PsbO (33 kDa), PsbP (23 kDa), and PsbQ (17 kDa). Additionally, the 10-kDa PsbR protein has been found in plant PSII and anticipated to play a role in water oxidation, yet the physiological significance of PsbR has remained obscure. Using the Arabidopsis psbR mutant, we showed that the light-saturated rate of oxygen evolution is strongly reduced in the absence of PsbR, particularly in low light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
101
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 42 publications
6
101
1
1
Order By: Relevance
“…ami-RNA-psbr-2. Likewise, the data revealed that subunits PSBP and PSBQ were both diminished in amounts in conjunction with PSBR, in agreement with data obtained for Arabidopsis PSBR-deficient plants (Suorsa et al, 2006;Liu et al, 2009;Allahverdiyeva et al, 2013). On the other hand, other PSII core subunits or the minor core PSII light-harvesting proteins, LHCB4 and LHCB5, were not significantly altered in their protein ratios in both ami-RNA-psbr strains.…”
Section: Diminishment Of Psbr Expression Destabilizes the Binding Of supporting
confidence: 79%
See 3 more Smart Citations
“…ami-RNA-psbr-2. Likewise, the data revealed that subunits PSBP and PSBQ were both diminished in amounts in conjunction with PSBR, in agreement with data obtained for Arabidopsis PSBR-deficient plants (Suorsa et al, 2006;Liu et al, 2009;Allahverdiyeva et al, 2013). On the other hand, other PSII core subunits or the minor core PSII light-harvesting proteins, LHCB4 and LHCB5, were not significantly altered in their protein ratios in both ami-RNA-psbr strains.…”
Section: Diminishment Of Psbr Expression Destabilizes the Binding Of supporting
confidence: 79%
“…Moreover, those authors identified cross-links between PSBP and CP26. The tight interaction between PSBP and PSBR, as suggested earlier (Suorsa et al, 2006;Liu et al, 2009), is also confirmed in our study, as depletion of PSBR impacts the association of PSBP with the PSII-LHCII supercomplex (Fig. 7).…”
Section: Psbr Is Involved In Forming a Recognition Site For The Bindisupporting
confidence: 71%
See 2 more Smart Citations
“…The plants were grown for 4 weeks with irrigation every 4 days with a half-strength solution of inorganic salts of Murashige and Skoog medium 6 as described previously. 1 Thylakoid membranes were isolated from the leaves of Arabidopsis plants according to the method of Suorsa et al 7 Isolated thylakoid membranes were incubated in the following suspension buffer bubbled with NO 2 for 60 min at 25 C under illumination (100 mmol photons/m 2 /s) or in the dark. The suspension buffer contained 50 mM Hepes-KOH (pH 7.0), 15 mM NaCl 2 , 5 mM MgCl 2 , and 400 mM sucrose.…”
mentioning
confidence: 99%